2019
DOI: 10.1242/jcs.226001
|View full text |Cite
|
Sign up to set email alerts
|

The exocyst complex and Rab5 are required for abscission by localizing ESCRT III subunits to the cytokinetic bridge

Abstract: Cytokinesis is the final step of cell division following chromosome segregation that generates two daughter cells. The conserved exocyst complex is required for scission of the intercellular cytokinetic bridge, although the molecular mechanisms it employs in this process are unclear. We identify and validate the early endocytic GTPase Rab5 as interacting with the exocyst complex in mammalian cells. Rab5 localizes in the cytokinetic bridge and on the midbody ring in a manner similar to the exocyst complex. Depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 97 publications
(175 reference statements)
1
14
0
Order By: Relevance
“…Conversely, from the experiments using the secA null mutant, the increase in the cell surface is critical for cytokinesis. Previous studies have reported that the delivery of intracellular membrane vesicles to the cell membrane is required for constriction of the cleavage furrow in zebrafish, C. elegans embryos, Drosophila spermatocytes, and yeast (Li et al, 2006;Robinett et al, 2009;Giansanti et al, 2015;Wang et al, 2016;Kumar et al, 2019). As a candidate of the membrane vesicles source, Golgi-derived vesicles, lysosome, or endosome has been reported (Arden et al, 2007;Boucrot and Kirchhausen, 2007;Goss and Toomre, 2008;Montagnac et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, from the experiments using the secA null mutant, the increase in the cell surface is critical for cytokinesis. Previous studies have reported that the delivery of intracellular membrane vesicles to the cell membrane is required for constriction of the cleavage furrow in zebrafish, C. elegans embryos, Drosophila spermatocytes, and yeast (Li et al, 2006;Robinett et al, 2009;Giansanti et al, 2015;Wang et al, 2016;Kumar et al, 2019). As a candidate of the membrane vesicles source, Golgi-derived vesicles, lysosome, or endosome has been reported (Arden et al, 2007;Boucrot and Kirchhausen, 2007;Goss and Toomre, 2008;Montagnac et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Both Rab5 and exocyst complex subunits localize at the midbody ring in the cytokinetic bridge and are required for delivering the membrane abscising ESCRT-III machinery to this site to enable abscission. This work suggests that early endosomes could play roles in cytokinetic abscission in addition to the documented roles of secretory vesicles and recycling endosomes (Kumar et al, 2019b).…”
Section: Mechanism Of Cytokinesismentioning
confidence: 72%
“…Oocytes depleted of Rab5 display defective yolk protein internalization [47]. Interestingly, it was recently shown in C. elegans embryos that Rab5 was enriched at cleavage furrows [48]. Depletion of Rab5 in four-and six-cell embryos caused multinucleated blastomeres, revealing a role for Rab5 in cytokinesis in C. elegans [48].…”
Section: Rab5mentioning
confidence: 95%
“…Interestingly, it was recently shown in C. elegans embryos that Rab5 was enriched at cleavage furrows [48]. Depletion of Rab5 in four-and six-cell embryos caused multinucleated blastomeres, revealing a role for Rab5 in cytokinesis in C. elegans [48]. Notably, Rab5 was shown to be important for cell boundary formation during fly cellularization [49].…”
Section: Rab5mentioning
confidence: 99%